Visitors satisfaction on safety features and maintenance of park facilities at Taman Bandar Pasir Gudang, Johor - See, Yi Xuen (2019)
This study explores visitors satisfaction level on the facilities regarding park safety and maintenance attributes at Taman Bandar Pasir Gudang (TBPG). TBPG is one of the famous urban park in the state of Johor due to World Kite Festival. The objectives of this study are to identify the user satisfaction level on existing facilities and examine the relationship between user satisfaction level on existing facilities with park safety and maintenance attributes. A total of 400 respondents were collected using questionnaire. The results showed significant relationship in five aspects of park safety which are solitary, vision, security guard surveillance, barrier and material used, and also four aspects of maintenance which are standard of quality, regular maintenance schedule, prompt repair for broken facilities and service of park personnel. Recommendations such as installation of barrier, reinforcement of security guards surveillance and acceleration of prompt repair works are suggested to improve TBPG relation to park safety and maintenance. The results of this study assisted the management of the park to understand their weakness and provide recommendations to improve the safety and maintenance of the park.